Is There a Role for Mammalian Target of Rapamycin Inhibition in Renal Failure due to Mesangioproliferative Nephrotic Syndrome?. (5th April 2012) - Trimarchi, Hernán; Forrester, Mariano; Lombi, Fernando; Pomeranz, Vanesa; Iriarte, Romina; Raña, María Soledad; Young, Pablo
Abstract : Primary glomerulonephritis stands as the third most important cause of end-stage renal disease, suggesting that appropriate treatment may not be as effective as intended to be. Moreover, proteinuria, the hallmark of glomerular damage and a prognostic marker of renal damage progression, is frequently resistant to thorough control. In addition, proteinuria may be the common end pathway in which different pathogenetic mechanisms may converge. This explains why immunosuppressive and nonimmunosuppressive approaches are partly not sufficient to halt disease progression. One of the commonest causes of primary glomerulonephritis is mesangioproliferative glomerulonephritis. Among the triggered intracellular pathways involved in mesangial cell proliferation, the mammalian target of rapamycin (mTOR) plays a critical role in cell growth, in turn regulated by many cytokines, disbalanced by the altered glomerulopathy itself. However, when inhibition of mTOR was studied in rodents and in humans with primary glomerulonephritis the results were contradictory. In light of these controversial data, we propose an explanation for these results, to dilucidate under which circumstances mTOR inhibition should be considered to treat glomerular proteinuria and finally to propose mTOR inhibitors to be prospectively assessed in clinical trials in patients with primary mesangioproliferative glomerulonephritis, for which a satisfactory standard immunosuppressive regimen is still pending.